Electrospinning in water and in situ crosslinking of hyaluronic acid / cyclodextrin nanofibers: Towards wound dressing with controlled drug release. (1st March 2019) - Séon-Lutz, Morgane; Couffin, Anne-Claude; Vignoud, Séverine; Schlatter, Guy; Hébraud, Anne
Graphical abstract: Highlights: Hyaluronic acid / poly(vinyl alcohol) (HA/PVA) nanofibers were electrospun from aqueous solutions. Addition of cyclodextrin (CD) in electrospinning solutions stabilized the process. Fibrous membranes were stable in water after successful crosslinking using EDC/NHS. Naproxen was loaded into nanofibers by impregnation in water or supercritical CO2 . Drug was released over several days, with a maximum during the first 24 h. Abstract: Hyaluronic acid (HA) is widely investigated due to its high potential for wound dressing applications. The fabrication of biomimetic HA-based scaffolds by electrospinning is thus extensively studied. However, HA is often dissolved in toxic organic solvents to allow the efficient production of electrospun nanofibers. Indeed, although HA is soluble in water, its ionic nature leading to long-range electrostatic interactions and the presence of counter ions induce a dramatic increase of the viscosity of aqueous HA solutions without insuring enough chain entanglements necessary for a stable and efficient electrospinning. In this study, biocompatible insoluble HA-based nanofibers were fabricated by electrospinning in pure water. To this end, poly(vinyl alcohol) (PVA) was added as a carrier polymer and it was found that the addition of hydroxypropyl-βcyclodextrin (HPβCD) stabilized the process of electrospinning and led to the efficient formation of uniform nanofibrous scaffolds. An in situ crosslinking process of the scaffolds is also proposed, insuring a whole fabrication process without any toxicity. Furthermore, the beneficial presence of HPβCD in the HA-based scaffolds paves the way for wound dressing applications with controlled drug encapsulation-release properties. As a proof of concept, naproxen (NAP), a non-steroidal anti-inflammatory drug was chosen as a model drug. NAP was impregnated into the scaffolds either in aqueous solution or under supercritical CO2 . The resulting functional scaffolds showed a regular drug release profile along several days without losing the fibrous structure. This study proposes a simple approach to form stable HA-based nanofibrous scaffolds embedding HPβCD using water as the only solvent, enabling the development of safe functional wound dressings.